(untitled) (REMUNOM, 2026)
This study analyzes how the consolidation of inclusive education policies in Brazil has expanded access to mainstream education for students with disabilities, while also highlighting challenges related to teacher training and the organization of pedagogical practices in schools. In this context, the success of school inclusion depends, to a large extent, on teachers’ ability to develop pedagogical strategies that recognize and value the diversity present in educational settings. Based on this issue, this article aims to analyze the pedagogical challenges faced by elementary and secondary school teachers in implementing Inclusive Education, with an emphasis on the relationship between teacher training and teaching practices focused on serving students with disabilities. This is a qualitative study conducted through a case study at a public school located in the municipality of São Luiz Gonzaga, in the state of Rio Grande do Sul. Data were collected through semi-structured interviews with elementary school teachers and Special Education professionals, as well as observations conducted in the school setting. The data analysis revealed that, although teachers recognize the importance of school inclusion, challenges persist regarding the inadequacy of initial teacher training, the need for systematic professional development processes, and institutional limitations that impact the development of inclusive teaching practices. The results indicate that the implementation of inclusive education requires coordination between educational policies, training processes, and the reorganization of teaching practices in everyday school life. It is concluded that strengthening teacher training is a fundamental element for building more equitable educational environments capable of promoting the development and learning of all students.